A comparison of lower limb stiffness and mechanical muscle function in ACL-reconstructed, elite, and adolescent alpine ski racers/ski cross athletes - Matthew J. Jordan; Per Aagaard; Walter Herzog (Elsevier, 2018)
Purpose: The aim of this study was to compare mechanical muscle function in the eccentric/concentric phases of vertical bilateral jumping in anterior cruciate ligament-reconstructed (ACLR), elite (ELITE), and adolescent (ADOL) alpine ski racers and ski cross athletes. Methods: Alpine ski racers/ski crossers (ACLR: n = 12, age = 26.7 ± 3.8 years; ELITE: n = 12, age = 23.9 ± 3.0 years; ADOL: n = 12, age = 17.8 ± 0.7 years; females: n = 6 per group, males: n = 6 per group) performed 5 maximal countermovement jumps (CMJs) and 5 squat jumps. The ground reaction forces for each limb were analyzed using dual force plate recording to obtain body center of mass (BCM) velocity, displacement, and power. The eccentric deceleration (ECC) and concentric phases were determined from BCM velocity. CMJ net concentric and ECC impulses were calculated (body mass normalized) along with the peak and mean BCM power and maximal vertical jump height. CMJ lower limb stiffness (LLS) was determined by the slope of the ground reaction forces vs. the BCM displacement curve over the ECC phase. Concentric and ECC asymmetry indices were calculated for each leg, and the left vs. right LLS was compared. Outcome measures (reported as mean ± SD) calculated as a 5-jump mean were normalized to body mass and compared using an analysis of variance. Results: No between-group differences were found for peak and mean power or jump heights. There were no group differences for LLS or net concentric phase impulse, but the net ECC impulse was lower in the ADOL group compared with ELITE skiers (ADOL: 1.33 ± 0.32 Ns/kg; ELITE: 1.59 ± 0.16 Ns/kg; p < 0.05). Although no group differences were found for ECC asymmetry indices, a group × limb interaction was found for LLS (p < 0.01), which was systematically higher in the right vs. the left limb of ADOL skiers (right: 54.1 ± 17.9 N/m/kg; left: 48.7 ± 15.7 N/m/kg; p < 0.01). Conclusion: ADOL skiers demonstrated decreased ECC impulse and systematic right limb dominance in LLS compared with ACLR and ELITE skiers. The implication of these findings for injury and performance are unknown, but further investigation into these potential relationships is warranted. Keywords: Between-limb asymmetry, Injury prevention, Knee injuries, Muscle power, Vertical jump